Prevalence of Dementia among Elderly Patients attending Psychiatry OPD of Tertiary Care Hospital and its Association with Socio Demographic Variables - Nepal, S; Sapkota, N (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: World is graying. With the rise in life expectancy, the elderly population is increasing. At the same time, prevalence of dementia is also increasing as ageing is the main risk factor for dementia. This study aims to find out the prevalence of dementia among old age patients and associated variables among the elderly psychiatric outpatients in a tertiary care hospital. Material and Method: A total of 210 consecutive elderly (60 or more years) outpatients in psychiatric OPD were enrolled in a period of one year, after taking informed consent with caretakers. Mini Mental State Examination (MMSE) was done as screening tool for cognitive impairment. Diagnoses were made according to ICD-10 guidelines. Data was analysed using SPSS. Results: Out of 210 subjects, 50.95% were female, 43.8% were of age group 60-64 years. Prevalence of dementia was 11.4% among which Alzheimer's dementia constituted 70.8% of total cases of dementia followed by vascular dementia (25%). Significant association of dementia was seen with age, occupation and Mini Mental State Examination (MMSE) score. Among other psychiatric comorbidities, depression (36.7%) was found to be the commonest mental illness followed by Neurotic, stress related and somatoform disorders (13.8%) and Alcohol dependence syndrome (12.9%). Conclusion: This study concludes that significant number of elderly patients attending OPD of tertiary care hospital suffers from dementia and MMSE is a reliable tool to screen dementia in the elderly patients. J Psychiatrists’ Association of Nepal Vol .6(1), 2017, p.12-17